2021
DOI: 10.1155/2021/6659668
|View full text |Cite
|
Sign up to set email alerts
|

LIFU Alleviates Neuropathic Pain by Improving the KCC2 Expression and Inhibiting the CaMKIV–KCC2 Pathway in the L4–L5 Section of the Spinal Cord

Abstract: Effective treatment remains lacking for neuropathic pain (NP), a type of intractable pain. Low-intensity focused ultrasound (LIFU), a noninvasive, cutting-edge neuromodulation technique, can effectively enhance inhibition of the central nervous system (CNS) and reduce neuronal excitability. We investigated the effect of LIFU on NP and on the expression of potassium chloride cotransporter 2 (KCC2) in the spinal cords of rats with peripheral nerve injury (PNI) in the lumbar 4–lumbar 5 (L4–L5) section. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Both cellular and animal experiments have confirmed that LIFU not only affects the activation and depolarization of Ca 2+ and Na + ion channels on the cell membrane (Kubanek et al, 2016 ) but also upregulates the expression of brain-derived neurotrophic factor (BDNF) following central nerve injury (Yang et al, 2015 ; Ni et al, 2017 ; Blackmore et al, 2019 ). In a previous study, our team also confirmed that LIFU stimulation can activate the spinal cord neurocircuits (Liao et al, 2021a ) and increase the expression of KCC 2 of the spinal cords of neuropathic pain rats effectively (Liao et al, 2021b ). However, whether LIFU can activate the spinal cord neurocircuits, upregulate the expression of KCC 2 , and then alleviate spasticity post-SCI spasm is still not completely clear.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Both cellular and animal experiments have confirmed that LIFU not only affects the activation and depolarization of Ca 2+ and Na + ion channels on the cell membrane (Kubanek et al, 2016 ) but also upregulates the expression of brain-derived neurotrophic factor (BDNF) following central nerve injury (Yang et al, 2015 ; Ni et al, 2017 ; Blackmore et al, 2019 ). In a previous study, our team also confirmed that LIFU stimulation can activate the spinal cord neurocircuits (Liao et al, 2021a ) and increase the expression of KCC 2 of the spinal cords of neuropathic pain rats effectively (Liao et al, 2021b ). However, whether LIFU can activate the spinal cord neurocircuits, upregulate the expression of KCC 2 , and then alleviate spasticity post-SCI spasm is still not completely clear.…”
Section: Introductionsupporting
confidence: 64%
“…LIFU stimulation of the spinal cord was performed as described previously (Liao et al, 2021a , b ). Briefly, before LIFU treatment, the hair around the ultrasonic irradiation site on the back of each rat was shaved off.…”
Section: Methodsmentioning
confidence: 99%
“…The LIFU stimulation procedure was performed as follows [ 29 ]: after anesthesia, the rats were fixed on a table, and the hair on their backs was removed using a depilating cream to expose the L4–L5 segments of the spinal cord. An ultrasound probe was fixed to the back of the L4–L5 spinal cord segment with a clapper.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that the evidence of other studies may give some hints. For example, several previous reports have reported that activation of the CaMKII/IV-CREB pathway in the SCDH contributes to NP through increasing the level of brain-derived neurotrophic factor, neuropeptides, and NMDA receptor or decreasing GABAergic transmission in SCDH ( 33 , 34 , 52 , 53 , 54 ). In addition, i.t.…”
Section: Discussionmentioning
confidence: 99%